Pengaruh Keselamatan & Kesehatan Kerja, Lingkungan Kerja, dan Displin Kerja Terhadap Kinerja Karyawan PT. Hakamindo Petro Chem - Ariyanto, Ariyanto; Bahri, Mohammad Saiful; Widayanto, Mutinda Teguh (Universitas Panca Marga, 2024)
Occupational safety and health, work environment, and work discipline need to be considered by every company to improve employee performance. This study aims to determine the relationship and influence between occupational safety and health, work environment, and work discipline on the performance of employees of PT Hakamindo Petro Chem using associative quantitative research methods. PT Hakamindo Petro Chem employees as many as 36 employees are the population in this study and the sampling technique uses saturated sampling technique with 36 employees as samples in this study. Likert scale is used as data collection and measurement in this study. The data sources in this study come from primary and secondary data. Methods for obtaining research data, researchers used observation, documentation, and questionnaire methods. Furthermore, the data that has been obtained is analyzed using validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of hypothesis testing in this study have proven that there is a positive and significant influence between occupational safety and health, work environment, and work discipline partially and simultaneously on employee performance, the results of this study also show that work safety has a dominant influence on employee performance